2021
DOI: 10.3389/fneur.2021.663353
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Cranial CT Imaging in Patients With Headache at the Emergency Department

Abstract: Background: Headache is among the most prevalent complaints in patients presenting to the emergency department (ED). Clinicians are faced with the difficult task to differentiate primary (benign) from secondary headache disorders, since no international guidelines currently exist of clinical indicators for neuroimaging in headache patients.Methods: We performed a retrospective review of 501 patients who presented at the ED with headache as a primary complaint between April 2018 and December 2018. Primary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
4
1
Order By: Relevance
“…Extra-cranial lesions were detected in more than half of patients compared to intracranial lesions. [8,17,19,[25][26][27] e findings of the present study corroborate with Rai et al [8] who reported a similar pattern of extra-cranial lesions and intracranial lesions. ere was no statistical difference in the proportion of patients diagnosed with sinusitis and brain neoplasm (tumor, metastasis, and cyst) when CT was contrast enhanced.…”
Section: Discussionsupporting
confidence: 92%
“…Extra-cranial lesions were detected in more than half of patients compared to intracranial lesions. [8,17,19,[25][26][27] e findings of the present study corroborate with Rai et al [8] who reported a similar pattern of extra-cranial lesions and intracranial lesions. ere was no statistical difference in the proportion of patients diagnosed with sinusitis and brain neoplasm (tumor, metastasis, and cyst) when CT was contrast enhanced.…”
Section: Discussionsupporting
confidence: 92%
“…We found that age > 40 years, smoking, signs/symptoms of infection, and nausea significantly increased the risk of abnormal headache-related findings in MRI, whereas numbness and history of migraine reduced this same risk. Of these factors, older age and nausea were the only ones reported in the previous CT and MRI scores [6,8,9,11]. A focal neurological deficit was reported as a major risk factor in every CT score, but this was not the case in our data.…”
Section: Discussioncontrasting
confidence: 67%
“…Moreover, our data showed various, less common causes that were not met in the previous smaller sample, including Chiari 1 malformation, arterial dissection and occlusion, PRES and signs of intracranial hypotension. When compared to the previous studies using CT for acute headaches, they reported similar prevalences of cerebrovascular conditions (intracranial hemorrhages and ischemia) and newly detected neoplasms, but a lower prevalence of conditions that are more identifiable by MRI (such as infectious diseases and intracranial hypertension) [6][7][8]. We found recent infarcts (identified with DWI) in 30 patients (4% of all, 22% of those with significant findings).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations